The Iron Empire - Dashner, James 1972- (New York, New York : Scholastic, 2014)
They've sailed on the Santa Maria, defended famous cities from Vikings and Mongols, and come face to face with some of the greatest figures in history. Now, at long last, Dak, Sera, and Riq travel back in time to the moment it all began. Their mission: to save the life of young Alexander the Great. But they are not the only time travelers in ancient Greece. An epic battle against their most dangerous foe awaits them, and history will be written by the victors. Fix the past. Save the future. It's now or never!
830L
105654
Keywords: Alexander -- the Great -- 356 B.C.-323 B.C -- Fiction; To 146 B.C.; Time travel -- Juvenile fiction; World history -- Juvenile fiction; Adventure and adventurers -- Fiction; Science fiction; Best friends -- Fiction; Adventure fiction; Conspiracies -- Fiction; Friendship -- Fiction; Greece -- History -- To 146 B.C. -- Juvenile fiction; Adventure stories; Children's stories; Fantasy fiction; Fiction; History; Juvenile works